Depression, Anxiety, and Coping In Peripartum Women During Covid-19 Pandemic - Hancheva C.; Bikovska P. (Acta Medica Bulgarica)
The World Health Organization declared pregnant women and mothers of infants to be among the most vulnerable groups during the COVID-19 pandemic. This study, a part of a large international prospective study, aimed to 1) evaluate the levels of perinatal depression and anxiety, 2) determine the risk and protective factors that predict perinatal mental health outcomes, and 3) ascertain the possible effects of different behavioral coping strategies to overcome stress and challenges during Covid-19 lockdowns and restrictions.